2015
DOI: 10.1360/n032015-00162
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the nanoscale morphology in the active layers of polymer solar cells

Abstract: Nanoscale structural and electronic evolution for increased efficiency in polymer solar cells monitored by electric scanning probe microscopy Chinese Science Bulletin 59, 360 (2014); Enhanced efficiency of perovskite solar cells through improving active layer morphology by interfacial engineering SCIENCE CHINA Chemistry 58, 830 (2015); Inverted polymer solar cells with TiO 2 electron extraction layers prepared by magnetron sputtering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In the OSCs field, using solvent additives is a more convenient strategy to improve the PCE of bulk heterojunction (BHJ) solar cells. Generally, solvent additives can not only achieve effective exciton dissociation but also improve the charge transport by adjusting molecular aggregation. Wang et al reported that the addition of DIO as an additive can reduce molecular aggregation and the domain size in PBDTTT-C:PC71BM, finally promoting the exciton dissociation and improving charge transport .…”
Section: Introductionmentioning
confidence: 99%
“…In the OSCs field, using solvent additives is a more convenient strategy to improve the PCE of bulk heterojunction (BHJ) solar cells. Generally, solvent additives can not only achieve effective exciton dissociation but also improve the charge transport by adjusting molecular aggregation. Wang et al reported that the addition of DIO as an additive can reduce molecular aggregation and the domain size in PBDTTT-C:PC71BM, finally promoting the exciton dissociation and improving charge transport .…”
Section: Introductionmentioning
confidence: 99%